Dichoropetalum andacii (Apiaceae), a new species from Türkiye - Akpulat, H. Aşkin; Ecevi̇t-Genç Gülay; Akalin Emi̇ne; Özcan, Taner (Phytotaxa, 2024)
Dichoropetalum andacii Akpulat, G. E. Genç & Akalın is described as a new species from Antalya, Türkiye. The new species differs from the similar D. chryseum and D. palimbioides by the number of umbel rays and bracteoles, fruit size, mericarp features, and by some ITS sequence differences. Diagnostic morphological and anatomical characters, karyological features, molecular structure of ITS region, and micromorphological structures of mericarps and pollens are discussed. Also, notes are presented regarding its phenology, ecology, and conservation status.